Studies on the Effect of Laser Shock Peening Intensity on the Mechanical Properties of Wire Arc Additive Manufactured SS316L - Geethapriyan Thangamani; Santosh Kumar Tamang; Md Saad Patel; Jinoop Arackal Narayanan; Muthuramalingam Thangaraj; Jufan Zhang; Pardeep Kumar Gianchandani; Palani Iyamperumal Anand (Journal of Manufacturing and Materials Processing)
This study examines the impact of laser shock peening (LSP) on the mechanical properties, microstructural features, and elemental distribution of stainless steel 316L (SS316L) produced using wire arc additive manufacturing (WAAM). The investigation focuses on significant changes in mechanical behavior, surface topography, and porosity following LSP treatment, comparing these results to the untreated condition. LSP treatment significantly enhanced the ultimate tensile strength (UTS) and yield strength (YS) of WAAM-fabricated SS316L samples. The UTS of the as-manufactured WAAM specimen was 548 MPa, which progressively increased with higher LSP intensities to 595 MPa for LSP-1, 613 MPa for LSP-2, and 634.5 MPa for LSP-3, representing a maximum improvement of 15.8%. The YS showed a similar trend, increasing from 289 MPa in the as-manufactured specimen to 311 MPa (LSP-1) and 332 MPa (LSP-2), but decreasing to 259 MPa for LSP-3, indicating over-peening effects. Microstructural analysis revealed that LSP induced severe plastic deformation and reduced porosity from 14.02% to 4.18%, contributing to the improved mechanical properties. Energy dispersive spectroscopy (EDS) analysis confirmed the formation of an oxide layer post-LSP, with an increase in carbon (C) and oxygen (O) elements and a decrease in chromium (Cr) and nickel (Ni) elements on the surface, attributed to localized pressure and heat impacts. LSP-treated samples exhibited enhanced mechanical performance, with higher tensile strengths and improved ductility at higher laser intensities. This is due to LSP effectively enhancing the mechanical properties and structural integrity of WAAM-fabricated SS316L, reducing porosity, and refining the microstructure. These improvements make the material suitable for critical applications in the aerospace, automotive, and biomedical fields.